Increased Risk of Progression of Coronary Artery Calcification in Male Subjects with High Baseline Waist-to-Height Ratio: The Kangbuk Samsung Health Study - Oh, Hyung-Geun; Nallamshetty, Shriram; Rhee, Eun-Jung (Diabetes & metabolism journal, 2016)
The waist-to-height ratio (WHtR) is an easy and inexpensive adiposity index that reflects central obesity. In this study, we examined the association of baseline WHtR and progression of coronary artery calcification (CAC) over 4 years of follow-up in apparently healthy Korean men. A total of 1,048 male participants (mean age, 40.9 years) in a health-screening program in Kangbuk Samsung Hospital, Seoul, Korea who repeated a medical check-up in 2010 and 2014 were recruited. Baseline WHtR was calculated using the value for the waist in 2010 divided by the value for height in 2010. The CAC score (CACS) of each subject was measured by multi-detector computed tomography in both 2010 and 2014. Progression of CAC was defined as a CACS change over 4 years greater than 0. During the follow-up period, progression of CAC occurred in 278 subjects (26.5%). The subjects with CAC progression had slightly higher but significant baseline WHtR compared to those who did not show CAC progression (0.51±0.04 vs. 0.50±0.04, P<0.01). The proportion of subjects with CAC progression significantly increased as the baseline WHtR increased from the 1st quartile to 4th quartile groups (18.3%, 18.7%, 28.8%, and 34.2%; P<0.01). The risk for CAC progression was elevated with an odds ratio of 1.602 in the 4th quartile group of baseline WHtR even after adjustment for confounding variables (95% confidence interval, 1.040 to 2.466). Increased baseline WHtR was associated with increased risk for CAC progression. WHtR might be a useful screening tool to identify individuals at high risk for subclinical atherosclerosis.